(untitled) (UCC Student Medical Journal, 2024)
Introduction: Spondyloarthritis is a group of arthritic diseases that classically manifest as inflammation of the sacroiliac and limb joints, as well as the axial skeleton. Microscopic bowel inflammation is identifiable in over 50% of these patients. Calprotectin measured in the serum and stool is an emerging surrogate marker of disease activity and/or bowel inflammation in spondyloarthritis. Objective: This article aims to review published literature to determine the accuracy of serum and faecal calprotectin levels for use in monitoring bowel inflammation and spondyloarthritis disease activity. Methods: Boolean operator strategy was used to search two databases (Embase and PubMed) and 52 relevant articles were identified. Duplicate results were eliminated, inclusion and exclusion criteria were applied. Results: Ten studies met the inclusion criteria and were summarized and analyzed. The EBL Validity questionnaire was applied to determine study quality. All research articles found calprotectin to be elevated in spondyloarthritis patients when compared to controls. Faecal calprotectin was superior in detecting disease activity and correlated with disease activity questionnaires, radiology and endoscopy results. Only one study assessed the effect of treatment on calprotectin and its correlation to bowel inflammation. Conclusion: Faecal calprotectin shows promise as a surrogate marker for disease activity and bowel inflammation in spondyloarthritis. Future studies should focus on the effect of treatment on faecal calprotectin and whether some treatments are better at preventing the progression of bowel inflammation in addition to treating spondyloarthritis. Supplementary investigations are needed to identify whether faecal calprotectin is useful as a marker of disease activity in response to treatment.